Evaluation of empirical pretreatment assessments for developing treatments for expulsion in pediatric feeding disorders. (1st December 2022) - Scotchie, Michaela; Borrero, Carrie S. W.
Abstract: A common problem among children with feeding disorders is expulsion (removing or spitting food or drink from the mouth), which interferes with treatment success when the goal is consumption. Previous research has identified effective treatments to reduce expulsion, most commonly—re‐presentation (presenting the expelled bite or a new bite of the same food immediately following the expulsion). However, there is not currently an assessment model in place to inform treatment decisions with a goal to reduce expulsion. In the present study, we used a multielement design to identify conditions under which little or no expulsion occurred with three children with feeding disorders. The results of the assessment were then used to inform treatment selection aimed to eliminate expulsion. The comparisons of the assessment included physical prompt, bite number, texture, preference, bite presentation style, and size of the bite. Results suggest that this assessment was useful for the design of individualized treatments for children who frequently expel food.